Accountability as Governance: Negotiating Performance, Power, and Bureaucratic Culture through SAKIP in Bali - Sunah, Aziza Azmilatus; Yudartha, I Putu Dharmanu (Universitas Pattimura, 2025)
This article explores the dynamics of Public Sector Performance Management through the implementation of the Government Agency Performance Accountability System (SAKIP) within the Organizational Bureau of the Bali Provincial Secretariat. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and document analysis. The study adopts Hatry’s five performance management indicators—input, output, outcome, efficiency, and effectiveness—as analytical lenses. Findings indicate that SAKIP has been systematically implemented, supported by organizational structure, performance-based budgeting, and an electronic information system (e-SAKIP). Key performance indicators have reached 100% achievement, demonstrating effective performance governance. However, challenges remain, particularly in cross-unit integration and human resource capacity. SAKIP is evolving from a compliance-oriented tool into a reflective instrument that fosters a data-driven accountability culture. The novelty of this study lies in its analysis of the interplay between performance indicators and local bureaucratic culture, emphasizing that successful implementation depends on the synergy of strategic planning, meaningful measurement, and transparent, outcome-oriented evaluation. The study recommends bureaucratic reform that embeds accountability values into organizational behavior and the development of integrated information systems to enhance long-term effectiveness. Accountability should thus be viewed not merely as an administrative requirement, but as a strategic governance process shaping performance-driven public institutions.